Predictive Value of Preoperative Endoscopic Ultrasound (EUS) After Neoadjuvant Chemotherapy in Locally Advanced Esophagogastric Cancer – Data From a Randomized German Phase II Trial - Sivanathan, Visvakanth; Utz, Christoph; Thomaidis, Thomas; Förster, Friedrich; Stahl, Michael; Lordick, Florian; Ibach, Stefan; Kanzler, Stephan; Adler, Andreas; Mönig, Stefan Paul; Schimanski, Carl C.; Ignee, Andre; Dietrich, Christoph F.; Galle, Peter R.; Moehler, Markus (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Purpose The role of EUS before or after neoadjuvant chemotherapy (nCTX) in advanced esophagogastric cancer (EGC) is still unclear. The phase II NEOPECX trial evaluated perioperative chemotherapy with or without panitumumab in this setting. The aim of this sub-study was to investigate the prognostic value of EUS-guided preoperative staging before and after nCTX.Materials and Methods Preoperative yuT/yuN stages by EUS were compared with histopathological ypT/ypN stages after curative resection. Reduction in T-stage from baseline to preoperative EUS was defined as downstaging (DS+) and compared to progression-free (PFS) and overall survival (OS) of patients without downstaging (DS-). In addition, preoperative EUS N-stages (positive N+ or negative N-) were correlated with clinical data.Results The preoperative yuT-stage correlated with the ypT-stage in 48% of cases (sensitivity 48%, specificity 52%), while the preoperative yuN-stage correlated with the ypN-stage in 64% (sensitivity 76%, specificity 52%). Within DS+ patients who were downstaged by ≥ 2 T-categories, a trend towards improved OS was detected (median OS DS+: not reached (NR), median OS DS-: 38.5 months (M), p=0.21). Patients with yuN+ at preoperative EUS had a worse outcome than yuN- patients (median OS yuN-: NR, median OS yuN+: 38.5 M, p = 0.013).Conclusion The diagnostic accuracy of EUS to predict the response after nCTX in patients with advanced EGC is limited. In the current study the endosonographic detection of lymph node metastasis after nCTX indicates a poor prognosis. In the future, preoperative EUS with sectional imaging procedures may be used to tailor treatment for patients with advanced EGC.
Keywords: Mortality; Locally advanced esophagogastric cancer; Endosonography; THEMES; staging